Friday

July 31, 2015

July 31, 2015

Posted by **Anonymous** on Tuesday, October 9, 2012 at 11:02am.

- geometry -
**Henry**, Wednesday, October 10, 2012 at 8:54pmA(x1,y1),B(x2,y2),C(x3,y3).

A(x1,0), B(-2,0), C(x3,0).

AB = BC

-2-x1 = x3+2.

-x1-x3 = 4

Eq1: x1+x3 = -4.

In Eq1,Letx1 = -6:

-6 + x3 = -4

x3 = 2.

A(-6,0), B(-2,0), C(2,0).

In Eq1, Let x1 = -4.

-4 + x3 = -4

x3 = 0.

A(-4,0), B(-2,0), C(0,0).

NOTE: Values chosen for X1 should be less than -2 so the numbers on the line increases to the right.